Effect of Health Education on Community Participation to Eradicate Aedes aegypti-Breeding Sites in Buahbatu and Cinambo Districts, Bandung - Elsa, Zahratul; Sumardi, Uun; Faridah, Lia (UI Scholars Hub, 2017)
Dengue hemorrhagic fever (DHF) is still a major public health problem in many regions in Indonesia including Bandung City. Community participation in implementing Eradication of Mosquito-Breeding Sites is still needed as it is considered the most effective method in controlling the dengue fever. This study aimed to determine the influence of health education towards community participation to eradicate mosquito-breeding sites, which was measured by knowledge level and larva index conducted in Bandung, specifically in two different locations with the highest and the lowest incidence rates of DHF. This study used quasi-experimental method. Samples were 100 people living in Cijawura and Cisaranten Wetan Subdistricts taken by using purposive sampling technique. Pre-test results showed that knowledge level of respondents in both subdistricts was significantly increasing (p value = 0.000) after health education was given. Container index (CI) and House index (HI) values in Cijawura Subdistrict were 13.2% and 26.7% respectively, then 9.6% and 28.4% respectively in Cisaranten Wetan Subdistrict. After the health education, CI value in Cijawura and Cisaranten Wetan Subdistricts significantly decreased (p value < 0.05), but HI value did not (p value > 0.05).